Determination of Banking Micro Variables for Indonesia's Economic Growth - Oktaviani, Lola; Aminda, Renea Sinta; Sundarta, M. Imam (Manager : Jurnal Ilmu Manajemen, 2025)
This study aims to examine the influence of banking micro variables on Indonesia's economic growth during the 2019–2023 period. The study focuses on three main independent variables: asset growth, capital structure measured by Debt to Equity Ratio (DER), and profitability measured by Return on Equity (ROE). The dependent variable is economic growth, which is represented by Gross Domestic Product (GDP). This study uses a quantitative method using secondary data sourced from the annual financial statements of ten banking companies listed on the Indonesia Stock Exchange and GDP data obtained from the Central Statistics Agency. Data analysis involves regression of panel data along with testing of classical assumptions and hypotheses. The findings show that the growth of assets and capital structure has a negative and significant impact on economic growth, while profitability has a positive and significant influence. These results suggest that while asset expansion and increased debt may not directly drive national economic growth, increased profitability in the banking sector can contribute positively to economic development. This research provides insight into how micro-level banking performance can affect macroeconomic outcomes, particularly in developing countries such as Indonesia.